1998
DOI: 10.1121/1.421127
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and intensity discrimination measured in a maximum-likelihood procedure from young and aged normal-hearing subjects

Abstract: A maximum-likelihood method was applied in measurements of frequency and intensity discrimination for aged and young normal-hearing subjects with closely matched audiograms. This method was preferred over other psychophysical procedures because it is efficient and controls experimental variance, features that are highly desirable for testing aged subjects. In order to implement the method, psychometric functions for each task were also measured from young subjects using a constant-stimuli procedure. For the yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
78
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 35 publications
23
78
6
Order By: Relevance
“…Age-related differences in the ability to detect these changes may be associated with poorer speech recognition (Buss et al, 2004). Several behavioral studies have reported an age-related decline in frequency difference limen, either as reduced frequency discrimination (He et al, 1998;Humes, 1996;Konig, 1957) or frequency modulation detection (He et al, 2007). However, substantial variability has been observed both within and across studies (see Jesteadt and Sims 1975, for a review).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Age-related differences in the ability to detect these changes may be associated with poorer speech recognition (Buss et al, 2004). Several behavioral studies have reported an age-related decline in frequency difference limen, either as reduced frequency discrimination (He et al, 1998;Humes, 1996;Konig, 1957) or frequency modulation detection (He et al, 2007). However, substantial variability has been observed both within and across studies (see Jesteadt and Sims 1975, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…However, substantial variability has been observed both within and across studies (see Jesteadt and Sims 1975, for a review). This variability may reflect differences in tasks and procedures, such as the standard frequency examined, and the subject's hearing sensitivity, level of attention, or ability to perform the task (He et al, 1998;Turner et al, 1982). For instance, He et al (1998) examined frequency discrimination in younger and older adults with normal hearing and observed a frequency-dependent aging effect, such that age-related differences were larger at lower frequencies than at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations